Eugenio Mendoza: a leader of 20th century industrialization in Venezuela - Valero Julio, Edgar (2022)
This article examines the genesis and consolidation of Empresas Mendoza, the most important industrial consortium of the 20th century in Venezuela. This group of companies was consolidated under the leadership of Eugenio Mendoza and had state support in the midst of booms and busts of an economy linked to oil revenues. The process in which, after a sustained economic growth, there was a weakening and crisis in the work culture and the discipline mechanisms of the workforce that had been effective initially is analyzed, as well as several problems that led to the extinction of this famous industrial group.